2018
DOI: 10.1080/1612197x.2018.1519839
|View full text |Cite
|
Sign up to set email alerts
|

Forced retirement transition: A narrative case study of an elite Australian Rules football player

Abstract: Retirement from elite sport is a complex and often-problematic process. The current study explores a negative case study of an athlete recently retired from a team sport (Australian Rules Football) in order to generate knowledge on how to improve the retirement process.Three semi-structured interviews were undertaken less than 5 years post retirement, and archival career records were gathered from online sources. Data were coded to construct a narrative account of the participant's career and retirement. Narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…There are many reasons why former professional athletes might experience depression. The transition to retirement is often difficult and it can be associated with a tremendous sense of loss ( 110 ), a void in meaning and purpose ( 111 , 112 ), and even financial hardship ( 113 ). Those former athletes who retire due to injury tend to have more difficulty with psychological adjustment to retirement than those who are more in control of their retirement decision ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reasons why former professional athletes might experience depression. The transition to retirement is often difficult and it can be associated with a tremendous sense of loss ( 110 ), a void in meaning and purpose ( 111 , 112 ), and even financial hardship ( 113 ). Those former athletes who retire due to injury tend to have more difficulty with psychological adjustment to retirement than those who are more in control of their retirement decision ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is not entirely clear why our study results differ from some of the prior literature. Although speculative, it is possible that some current study participants with shorter playing careers were forced to retire due to injury, and qualitative case studies of forced retirement in elite athletes have found it to be associated with a sense of loss, a struggle to find meaning, and depressive symptoms ( 71 , 72 ). In other words, one possible interpretation of the association between longer elite level rugby league careers and less perceived cognitive decline in the current study is that those athletes who play for more years are able to do so, in part, because they experience fewer serious sport-related injuries, while those who retire earlier face negative mental health consequences of doing so.…”
Section: Discussionmentioning
confidence: 97%
“…High-performance sports and career transitions post-athletic life have been widely studied in recent decades. This research covers various phases of an athlete's career, from shifts in training locations and moving from school to higher education, to transitioning from junior to senior competition levels and retirement (Park et al, 2013;Demetriou et al, 2018;Stambulova et al, 2021). In this context, considerable attention has been directed towards researching and understanding the consequences of retirement from competitive sports for athletes.…”
Section: Introductionmentioning
confidence: 99%